Bone-marrow plasma cell burden correlates with IgM paraprotein concentration in Waldenström macroglobulinaemia. Issue 6 (6th April 2011) - Pasricha, Sant-Rayn; Juneja, Surender K; Westerman, David A; Came, Neil A
Abstract : Aims: Correlations between the marrow histopathology and clinical findings in Waldenström macroglobulinaemia (WM) are not well defined, and the pathophysiology of the plasma cell involvement is poorly understood. The authors used a standardised immunohistological approach to the enumeration of B lymphocyte and plasma cell compartments in the bone-marrow trephine to investigate associations between bone-marrow morphology and clinical/laboratory indices. Methods: In 80 newly diagnosed, untreated cases of WM, the authors determined the degree and pattern of B lymphocyte (CD20+) and plasma cell (CD138+) infiltration in the bone-marrow trephine, as defined by immunohistochemistry, and correlated the disease in the marrow with components of the international scoring system for WM (age, serum IgM paraprotein level, haemoglobin, platelet count and β2 microglobulin). Plasma cell clonality was assessed by κ and λ staining. Results: Serum IgM paraprotein concentration was related to the plasma cell burden in the bone marrow (coefficient 0.231, p<0.005), but not the B lymphocytic infiltrate. Overall lymphoplasmacytic disease burden weakly correlated with severity of anaemia (coefficient 0.236, p=0.055). In 28/28 evaluated cases, plasma cells exhibited light chain restriction that was concordant with both that of the B lymphocytic infiltrate and paraprotein. Conclusions: Bone-marrow features, in particular the degree of plasma cell infiltration, correlate with IgM paraprotein concentration at diagnosis in WM. The plasma cell compartment in this condition appears to be part of the neoplastic clone. In WM, specific evaluation of the plasma cell compartment in the bone marrow at baseline and following therapy may be valuable.